THE EFFECT OF MULTIMEDIA DESIGN ON LEARNING AND PERCEPTION ACROSS THE LIFESPAN - Fenesi, Barbara (My University, 2015)
The goal of this dissertation was to examine the effect of multimedia design strategies on learning across the lifespan and across working memory capacities. The introduction outlines the main theoretical frameworks that constitute multimedia research, and the preliminary research that facilitated the articles represented in this sandwich thesis. The key contributions were 1) the replication of the negative effect of redundant text compared to complementary images on multimedia learning in younger adults, and an interesting reversal effect in older adults who benefited from redundant text and were impaired by images, 2) the finding that learners were unable to recognize ineffective presentations even when given direct exposure to both effective and ineffective designs, and 3) the demonstration that working memory capacity (WMC) predicted learning from various presentation designs—with poorly designed presentations selectively hindering low WMC learners, while pedagogically-sound presentation designs mediated differences in WMC and homologized performance.
Keywords: PhD Dissertation